2007
DOI: 10.1074/jbc.m609778200
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein rpS2 Is Hypomethylated in PRMT3-deficient Mice

Abstract: PRMT3 is a type I arginine methyltransferase that resides in the cytoplasm. A large proportion of this cystosolic PRMT3 is found associated with ribosomes. It is tethered to the ribosomes through its interaction with rpS2, which is also its substrate. Here we show that mouse embryos with a targeted disruption of PRMT3 are small in size but survive after birth and attain a normal size in adulthood, thus displaying Minute-like characteristics. The ribosome protein rpS2 is hypomethylated in the absence of PRMT3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 25 publications
8
101
0
Order By: Relevance
“…Interestingly, inhibition of methylation by Adox slightly increases the mobility of PRMT6, in contrast to all other PRMTs that were either unaffected within the limits of statistical significance (PRMT1 and 7), or decreased (PRMT2, CARM1/PRMT4, and most significantly, PRMT3). PRMT3 is known to methylate both nuclear and cytoplasmic proteins, such as the nuclear poly(A)-binding protein (PABPN1) (Fronz et al, 2008;Smith et al, 1999) and, most prominently, the cytoplasmic ribosomal protein S2 (rpS2) (Bachand and Silver, 2004;Choi et al, 2008;Swiercz et al, 2007;Swiercz et al, 2005). The localization in both compartments was therefore not a surprise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, inhibition of methylation by Adox slightly increases the mobility of PRMT6, in contrast to all other PRMTs that were either unaffected within the limits of statistical significance (PRMT1 and 7), or decreased (PRMT2, CARM1/PRMT4, and most significantly, PRMT3). PRMT3 is known to methylate both nuclear and cytoplasmic proteins, such as the nuclear poly(A)-binding protein (PABPN1) (Fronz et al, 2008;Smith et al, 1999) and, most prominently, the cytoplasmic ribosomal protein S2 (rpS2) (Bachand and Silver, 2004;Choi et al, 2008;Swiercz et al, 2007;Swiercz et al, 2005). The localization in both compartments was therefore not a surprise.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation of arginine residues appears to be a rather stable, but nonetheless dynamic modification (Bedford, 2007;Bedford and Richard, 2005;Fackelmayer, 2005b;Wysocka et al, 2006). It has been implicated in a large variety of important cellular functions, such as signaling (Berthet et al, 2002;Blanchet et al, 2006;Mowen et al, 2004;Xu et al, 2004), DNA repair (for a review, see Lake and Bedford, 2007), maturation and nucleocytoplasmic transport of RNA (Boisvert et al, 2002;Cheng et al, 2007;Shen et al, 1998;Yanagida et al, 2004), protein protection (Fackelmayer, 2005b), ribosomal assembly (Bachand and Silver, 2004;Swiercz et al, 2007;Swiercz et al, 2005) and the regulation of gene expression (e.g. An et al, 2004;Balint et al, 2005;Iberg et al, 2008;Xu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PRMT3 contains a unique C2H2 (Cys2His2)-type zinc finger in the N terminus, before the catalytic core (36). The prmt3 null mice displayed reduced embryo size, depicting Minute-like characteristics during organogenesis and fetal growth (37). Perturbation of PRMT3 expression in cultured rat hippocampal neurons caused deformed spines (38).…”
Section: Significancementioning
confidence: 99%
“…Using various deletions of rpS2, it was shown that PRMT3 methylates RG repeats in the N-terminus of rpS2, and disruption of the PRMT3 (Rmt3) gene in S. pombe resulted in viable cells with an increased ratio of free 60S ribosome subunit, suggesting a role for PRMT3 in ribosomal assembly Swiercz et al, 2005). Similarly, PRMT3 knockout mice are viable but the embryos are small and exhibit hypomethylation of rpS2 (Swiercz et al, 2007). Additionally, PRMT3 also interacts with the tumor suppressor DAL-1/4.1B (differentially expressed in adenocarcinoma of the Lung), which negatively modulates its methyltrasnferase activity (Singh et al, 2004).…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%